Prooszę Was.!
;/
Rozwiąż równania:

a) (3 - 2x) + +(3x + 4 ) = -(3-2x) + (5x + 4 )

b) -(x + 3) + (2x - 1) = (1 + 4x) + (3+x)

c) -(4 - 2x) - (2x + 4 ) = ( 3x - 1 ) + ( 2x - 5 ) - ( 7 - 3x )

d) ( 4 - x ) - ( 2x + 3 ) + ( x - 4 ) = -( 2x - 3 ) - -( x + 7 )

Pliiis .!
;/;/

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T22:46:43+01:00
A)
(3 - 2x) + (3x + 4 ) = -(3-2x) + (5x + 4 )
3-2x+3x+4=-3+2x+5x+4
-6x=-6
x=1


b)
-(x + 3) + (2x - 1) = (1 + 4x) + (3+x)
-x-3+2x-1=1+4x+3+x
-4x=8
x=-2

c)
-(4 - 2x) - (2x + 4 ) = ( 3x - 1 ) + ( 2x - 5 ) - ( 7 - 3x )
-4+2x-2x-4=3x-1+2x-5-7+3x
-8x=-5
x=5/8

d)
( 4 - x ) - ( 2x + 3 ) + ( x - 4 ) = -( 2x - 3 ) - ( x + 7 )
4-x-2x-3+x-4=-2x+3-x-7
x=-1
1 5 1